The challenge of change for innovation in construction: A North Cyprus perspective - N/A (Elsevier, 2007)
A vision of change for innovation within the perspective of revaluing the construction industry is essential to develop a culture of self-sustaining improvement, mutual recognition, respect and support in the long term in North Cyprus. The research attempts to put forward a case for a restructuring of the construction sector in order to deliver a step in change in quality of output and to realise maximum value to all clients, stakeholders and end users. The main objective of this study is to (1) determine current innovation practices and identify key issues that contribute to successful implementation (2) assess the existence and severity of barriers to change for innovation (3) propose solutions for overcoming barriers to change for innovation in construction industry and develop a framework to revaluate the construction industry. The research includes an extensive literature study, interviews with managers on the challenge of change for innovation in construction, analysis of this information to develop findings, and extending these to present the key strategic issues that could be targeted for revaluing the construction industry. The paper commences on understanding the firms’ own processes and detecting their weaknesses and strengths, determining the strategies and actions that should be made in the short term to adopt innovation practices and helping the North Cyprus construction industry to learn as a whole. The paper concludes how the drivers of change for innovation can offer benefits to construction firms in North Cyprus if appropriate strategies are adopted.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.buildenv.2005.10.032) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Change; Innovation; Revaluing construction industry; North Cyprus